2016
DOI: 10.7860/jcdr/2016/17236.8007
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Clavicle Fractures: A Report of Three Cases

Abstract: We have encountered three cases of bilateral clavicle fractures with different modes of trauma in three different age groups. One of these patients had a high-velocity roadside accident while the other case suffered a crush injury between a wall and a tractor. In the third case, a motorcycle fell over the patient. All of the fractures united well after conservative treatment with the return of normal functional activity. With the increasing incidence of high-energy trauma, we may encounter more of these injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Bilateral clavicle fractures could be missed because of their association with more severe chest injuries or a more symptomatically displaced fracture on one side or due to inadequate chest radiographs. Lakhotia, et al reported in their case series that fractures with various energy mechanisms were treated conservatively and returned to good functional outcomes without any complications [ 3 ]. Kulkarni, et al demonstrated in their study that intramedullary K-wire fixation at a single setting on both clavicle fracture showed good bridging callus formation and the full range of motion without any disturbance of daily activities [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral clavicle fractures could be missed because of their association with more severe chest injuries or a more symptomatically displaced fracture on one side or due to inadequate chest radiographs. Lakhotia, et al reported in their case series that fractures with various energy mechanisms were treated conservatively and returned to good functional outcomes without any complications [ 3 ]. Kulkarni, et al demonstrated in their study that intramedullary K-wire fixation at a single setting on both clavicle fracture showed good bridging callus formation and the full range of motion without any disturbance of daily activities [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although clavicle fractures represent 2–5% of all fractures in adults and accounting for > 10% in children [6] , [7] , bilateral clavicle fractures are rarely reported in the literature [8] , [9] . Most clavicle fractures have been managed non-surgically due to the high complication rates of the surgical treatment [10] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Bilateral clavicle fractures are usually described in the setting of polytrauma and are often missed due to other concomitant life-threatening injuries that draw all the attention. 3 In high-energy trauma cases and bilateral shoulder compression injuries, proper clinical assessment and chest radiographs including both shoulder joints should be performed, and bilateral clavicle fractures should be actively sought. 3 There is no general consensus on the modality of treatment of bilateral clavicle fracture.…”
Section: Introductionmentioning
confidence: 99%